Nurse Anesthetists’ Perceptions of the Airway Assessment of Patients with Obesity and the Impact of an Educational Intervention: A Quality Improvement Project - Sarah Elizabeth McGuire (My University, 2024)
As the prevalence of obesity increases, there are more patients with obesity presenting for surgery requiring anesthesia. The increased adiposity in obese patients alters anatomy and physiology and places them at higher risk for a difficult perioperative airway. There are a variety of techniques to properly assess these risks; however, no single source could be found that succinctly incorporated predictive scales for properly identifying and managing potential difficult airways in obese patients. This quality improvement project aimed to better understand CRNA perceptions of airway assessment techniques for patients with obesity. Perceptions of nurse anesthetists regarding methods for assessing the airways of patients with obesity before and after receipt of an educational resource and presentation were assessed using Qualtrics pre- and post-surveys. Results from the project showed increased access to education on airway assessment for obese patients, better awareness of evidence-based practices supported by AANA and ASA, more efficient access to clinical guidelines, and increased confidence among CRNAs in their knowledge of airway assessment. CRNAs also indicated a higher likelihood of using various airway assessment methods. Improving airway prediction accuracy can reduce prolonged PACU stays, hospital days, and postoperative intubations, lowering healthcare costs. The primary limitations of this quality improvement project were its small sample size and brief implementation period. Knowledge gained from this pilot project could be used in future quality improvement and policy efforts aimed at improving anesthesia care of obese patients.
None
Keywords: nurse anesthetist; obesity; bariatric; airway assessment; difficult airway